Les stèles mérovingiennes, premiers témoignages des communautés chrétiennes rurales d’Île-de-France - Stéphane Ardouin (Archéologie Médiévale)
Numerous Merovingian funerary steles have been excavated in Île-de-France, most notably in the North-Western part of this region, in an area encompassing the dioceses of Rouen, Paris, Evreux and Chartres. Inherited from an antique tradition, the Merovingian exemples are however more numerous. Most of them are bare of any inscription, though they are frequently ingraved with symbols, which vary from one grave site to the other. Numerous cross figures are found, variable in shapes and forms, alluding to Christian symbols, sometimes in a definitive way. Some of the motifs are more geometric, similar to the patterns found on plaster sarcophagi from Île-de-France. Dated from the 6th and 7th c. and often found in a different context than their original purpose, these steles are some of the earliest traces linked to the first rural Christian communities of the area, along with a few inscriptions and remaining vestige of buildings.